The diversity of data needed to drive design - Terne, M; Karlsson, J; Gustafsson, C (Refugee Studies Centre, University of Oxford, 2017)
The developers of the Refugee Housing Unit know every aspect and component of their design but can never know what it is like to wake up in one of them every day. Likewise, the end user does not have the tools or resources to make comprehensive changes to its design. The point is about how to work together on it.